A SYSTEMATIC REVIEW AND META‐ANALYSIS OF WILLINGNESS‐TO‐PAY VALUES: THE CASE OF MALARIA CONTROL INTERVENTIONS. (23rd April 2012) - Trapero‐Bertran, M.; Mistry, H.; Shen, J.; Fox‐Rushby, J.
ABSTRACT The increasing use of willingness to pay (WTP) to value the benefits of malaria control interventions offers a unique opportunity to explore the possibility of estimating a transferable indicator of mean WTP as well as studying differences across studies. As regression estimates from individual WTP studies are often assumed to transfer across populations it also provides an opportunity to question this practice. Using a qualitative review and meta analytic methods, this article determines what has been studied and how, provides a summary mean WTP by type of intervention, considers how and why WTP estimates vary and advises on future reporting of WTP studies. WTP has been elicited mostly for insecticide‐treated nets, followed by drugs for treatment. Mean WTP, including zeros, is US2.79 for insecticide‐treated nets, US6.65 for treatment and US2.60 for other preventive services. Controlling for a limited number of sample and design effects, results can be transferred to different countries using the value function. The main concerns are the need to account for a broader range of explanators that are study specific and the ability to transfer results into malaria contexts beyond those represented by the data. Future studies need to improve the reporting of WTP. Copyright © 2012 John Wiley & Sons, Ltd.